3PL performance evaluation and selection: a MCDM method. Issue 2 (2nd April 2016) - Aguezzoul, Aicha; Pires, Silvio
ABSTRACT: Third-party logistics (3PL) performance evaluation and selection is a strategic decision and a complex process that involves various qualitative and quantitative criteria. In this article, a multi-criteria decision-making (MCDM) tool based on ELECTRE I method is developed and applied to this process. This tool allows constructing a partial ranking, choosing a set promising 3PL and making the sensitivity analysis by varying the main parameters. An example of a real case is implemented to demonstrate the practicability of the proposed method.